Risk factors of colorectal cancer: the comparison of selected nutritional behaviors of medical and non-medical students - Dominika Malinowska; Robert Milewski; Małgorzata Żendzian-Piotrowska (BMC, 2023)
Abstract Background The aim of the study was to compare the diet of medical and non-medical students in relation to colorectal cancer risk factors. Material and methods The study included 239 students of various universities in Bialystok, Poland. Respondents were divided into four groups: students of dietetics at the Medical University (SD), students of other fields of study at the Medical University (SMUB), students of the University of Technology (SBUT) and students of the University of Bialystok (SUB). The research tool was an anonymous questionnaire in an electronic form, designed by the authors of this paper. Results Overweight was the least common among students of dietetics. Products that may increase the risk of developing colorectal cancer were most frequently consumed by students of non-medical universities. Everyday consumption of processed meat products was declared by 2.08% of SD, 24.00% of SMUB, 16.13% of SBUT and 25.93% of SUB. Red meat was consumed several times a week or every day by 25% of SD, 25.33% of SMUB, 48.39% of SBUT and 35.19% of SUB. Fast-food meals consumption once or several times a week was confirmed by 4.17% of SD, 18.67% of SMUB, 27.42% of SBUT and 38.89% of SUB. Conclusion The study conducted shows that students expose themselves to colorectal cancer risk factors through their diet.